Pelatihan Pengembangan Keterampilan dengan Memanfaatkan Software Photoshop Pada Karang Taruna Aksara RW17 Pancoran Mas Depok - Zulkarnain, Iskandar; Galih Whendasmoro, Raditya (HIMPUNAN DOSEN GEMILANG INDONESIA, 2022)
Graphic design is very useful for today's society, this can be seen in the development of the business world where the display of images in the form of banners or banners is used to help entrepreneurs in marketing their merchandise. This community service activity was carried out at Karang Taruna Aksara RW17 Pancoran Mas Village – Depok in the form of graphic design training using the adobe Photoshop application. This community service activity aims to help the youth of Karang Taruna Aksara RW17 in improving their knowledge and skills in the form of making advertisements and advertisements using the Adobe Photoshop application so that young people can become entrepreneurs. This service activity was carried out by the method of lectures on the substance of the activity, followed by the practice of operating Adobe Photoshop using a computer and testing the participants to find out to what extent they absorbed the training material that had been given. Based on the results of graphic design skills training activities, it is known that out of 18 participants15 people can understand, using the tools in Adobe Photoshop to design advertising and advertising products, namely invitations, banners, and business cards well